If a sequence oscillates, i.e. if its elements change signs, its sum can have weird behavior. Consider the following two oscillating sequences starting with k = 2 : { a k b k = 2 1 , − 2 1 , 4 1 , 4 1 , − 4 1 , − 4 1 , 8 1 , 8 1 , 8 1 , 8 1 , − 8 1 , − 8 1 , − 8 1 , − 8 1 … = 2 1 , − 2 1 , 8 1 , 8 1 , − 8 1 , − 8 1 , 2 4 1 , 2 4 1 , 2 4 1 , 2 4 1 , − 2 4 1 , − 2 4 1 , − 2 4 1 , − 2 4 1 … Question: Do their series k = 2 ∑ ∞ a k and k = 2 ∑ ∞ b k converge?
Note: Both sequences are formally defined by N I n a k = n = 0 ⋃ ∞ { 2 n ; … ; 2 n + 1 − 1 } = : { 1 } ∪ n = 1 ⋃ ∞ I n , = { 2 n ; … ; 2 n + 2 n − 1 − 1 } ∪ { 2 n + 2 n − 1 ; … ; 2 n + 1 − 1 } = : I n , 0 ∪ I n , 1 , n ≥ 1 = 2 n ( − 1 ) l , b k = n 2 n ( − 1 ) l , 2 ≤ k ∈ I n , l
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Observations
Proof: (last statement only) k ∈ I n , l ∑ a k = 2 n ( − 1 ) l ⋅ 2 n − 1 = 2 ( − 1 ) l , k ∈ I n , l ∑ b k = n 2 n ( − 1 ) l ⋅ 2 n − 1 = 2 n ( − 1 ) l
Convergence
Let A N : = ∑ k = 2 N a k , B N : = ∑ k = 2 n b k . Check A N first: N N = 2 m − 1 : = 2 m + 2 m − 1 − 1 : A N A N = k = 2 ∑ N a k = n = 1 ∑ m − 1 k ∈ I n ∑ a k = 0 = k = 2 ∑ N a k = n = 1 ∑ m − 1 k ∈ I n ∑ a k + k ∈ I m , 0 ∑ a k = 2 1
The sequence A N has two subsecquences A 2 m − 1 = 0 , A 2 m + 2 m − 1 − 1 = 2 1 with different limits - it cannot converge!
Let's tackle the other series with the Squeeze Theorem , take any N ∈ I m and calculate an upper estimate using the triangle inequality (*): 0 ≤ ∣ B N ∣ = ∣ ∣ ∣ ∣ ∣ k = 2 ∑ N b k ∣ ∣ ∣ ∣ ∣ = ∣ ∣ ∣ ∣ ∣ n = 1 ∑ m k ∈ I n ∑ b k + k = 2 m ∑ N b k ∣ ∣ ∣ ∣ ∣ ( ∗ ) ≤ k = 2 m ∑ N ∣ b k ∣ ≤ k ∈ I m ∑ ∣ b k ∣ = m 2 m 1 ⋅ 2 m = m 1 → 0 for m → ∞
Using the Squeeze Theorem, lim N → ∞ ∣ B N ∣ = 0 . It follows that lim N → ∞ B N = 0 .
We proved k = 2 ∑ ∞ a k diverges, k = 2 ∑ ∞ b k converges
Notes and common mistakes